2009
DOI: 10.1038/bmt.2009.328
|View full text |Cite
|
Sign up to set email alerts
|

New perspectives on the biology of acute GVHD

Abstract: The use of allogeneic hematopoietic cell transplantation (HCT) has increased as new techniques have been developed for transplantation in patients who previously would not have been considered HCT candidates. However, its efficacy continued to be limited by the development of frequent and severe acute GVHD. The complex and intricate pathophysiology of acute GVHD is a consequence of interactions between the donor and host innate and adaptive immune responses. Multiple inflammatory molecules and cell types are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
126
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(131 citation statements)
references
References 146 publications
1
126
0
Order By: Relevance
“…It has been reported that dendritic cells (DCs) are a type of APC that have the strongest antigen-presenting ability and can uniquely activate naive T cells, leading to acute graft rejection. 1,5 DCs in an immature state demonstrate significantly less antigenpresenting ability, and reduced DCs in a mixed allogeneic Tcell lymphocyte reaction lead to weak T-cell proliferation with a reduced occurrence of GVHD. In addition to human leukocyte antigen mismatching between donors and recipients being the main reason of GVHD, bacterial infections are also an important inducing factor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that dendritic cells (DCs) are a type of APC that have the strongest antigen-presenting ability and can uniquely activate naive T cells, leading to acute graft rejection. 1,5 DCs in an immature state demonstrate significantly less antigenpresenting ability, and reduced DCs in a mixed allogeneic Tcell lymphocyte reaction lead to weak T-cell proliferation with a reduced occurrence of GVHD. In addition to human leukocyte antigen mismatching between donors and recipients being the main reason of GVHD, bacterial infections are also an important inducing factor.…”
Section: Introductionmentioning
confidence: 99%
“…The complex and intricate pathophysiology of acute GVHD is a consequence of interactions between the donor and host innate and adaptive immune responses. 1 Activation of donor T cells by antigen-presenting cells (APCs) is the most important among the three stages described in acute GVHD, as the activated T cells migrate to target organs and cause damage in the recipient target tissue. 2 It has been reported that both host-derived and donor-derived APCs are present in secondary recipient lymphoid tissues after allogeneic bone marrow transplantation (BMT).…”
Section: Introductionmentioning
confidence: 99%
“…From a biological point of view, the results are reliable. Others have reasoned that Th2 cell therapy could rapidly ameliorate severe aGvHD via IL-4 and IL-10 mediated mechanisms [19] [20]. It is noteworthy that in our study a set of genes, indicated by computational analysis, included same mediators of Th2 response such as IL10, and signal transducer and activator of transcription 6, interleukin-4 induced (STAT6).…”
Section: Biomedical Conclusion and Future Workmentioning
confidence: 90%
“…This evidence is supported by a previous report about ICOS as regulatory molecule for T cell responses during aGvHD. It has been showed that ICOS signal inhibits aGvHD development mediated by CD8 positive effector cells in HSCT [20]. According to previous reports, mediators of apoptosis cells and dendritic cell activators were involved.…”
Section: Biomedical Conclusion and Future Workmentioning
confidence: 99%
“…Furthermore, the timing and duration of cytokine expression may be a critical factor determining the induction of the graft-versus-host (GvH) reaction, and cytokine dysregulation could potentially contribute to the severity of GvHD. Recently, Choi et al (2010) and Paczesny et al (2010) reviewed the biology of acute GvHD, and concluded that the underlying mechanisms of GvHD have emerged as a complex network of immune interactions where the key players are the naive T cells, the host and donor APCs, CTLs and regulatory T cells, along with new players such as Plasmacytoid DCs (pDCs), B cells and Th17 cells.…”
Section: Role Of Cytokines In Graft-versus-host Disease After Allogenmentioning
confidence: 99%